Effects of light quality on rutin production and growth of Physalis angulata (Linn.) seedlings cultured in vitro - Souza, Herbert Cristian de; Filho, Luís Cláudio Kellner; de Brito, Marlete Ferreira; Hara, Alessandra Cristina Boffino de Almeida Monteiro; Donadon, Maria Leonor Beneli [UNESP]; Pietro, Rosemeire Cristina Linhari Rodrigues [UNESP]; Januário, Ana Helena; Silva, Fabiano Guimarães (Southern Cross Publishing, 2019)
Physalis angulata Linn. is a plant with great importance in folk medicine for its various therapeutic properties and the production of active compounds. It is known as camapú in Brazil. The P. angulata seedlings were cultured in vitro under different light qualities such as white (control), blue, green, red, and yellow at 16 h photoperiod. After 30 days of culture, the shoot length, number of leaves, fresh and dry matter and rutin content were evaluated in triplicate in methanol extracts of seedlings exposed to the different lights by High-Performance Liquid Chromatography- Diode Array (HPLC-DAD). The mean shoot length was longer in seedlings cultured under yellow light (22.83 ± 0.65 cm, 1.62-fold), red light (22.58 ± 0.44 cm, 1.6-fold), or green light (20.57 ± 0.72 cm, 1.46-fold) than seedlings exposed to white light (14.13 ± 0.26 cm). There were no differences in the mean number of leaves between seedlings grown under the remaining lights and white light. Fresh (1,152 ± 0.16 g) and dry weight (0.078 ± 0.01 g) were higher in seedlings grown under white light. However, rutin production was higher under blue light (2.78 ± 0.05 μg g -1 by dry weight) and green light (2.40 ± 0.06 μg g -1 by dry weight). Therefore, the various light qualities affected the growth of P. angulata seedlings differently under in vitro culture condition. The blue and green lights promoted greater accumulation of rutin in this species.
Keywords: Light quality; Physalis angulata; Rutin; Tissue culture